2014
DOI: 10.1002/jobm.201400368
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an N‐glycosylated Bacillus subtilis leucine aminopeptidase expressed in Pichia pastoris

Abstract: Aminopeptidase is an important flavorsome especially in protein hydrolysate debittering by removing hydrophobic amino acid residue at the N-terminal end. Besides, it is also applied to preparation of active peptides and analysis of protein sequence. In this study, leucine aminopeptidase from Bacillus subtilis was cloned and expressed in Pichia pastoris, a widely used heterologous protein expression host. Then it was purified and characterized. After methanol induction for 96 h, the aminopeptidase activity in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Of these, only one N-glycosylation site showed a significant difference in abundance levels between CYLT and YLT, N 577 (CYLT:YLT = 3.63). Previous studies found that N-glycosylated aminopeptidases exhibited higher thermal stability and catalytic efficiency . This study demonstrated that N-glycosylation would promote aminopeptidase catalysis to increase the level of protein degradation in CYLT.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Of these, only one N-glycosylation site showed a significant difference in abundance levels between CYLT and YLT, N 577 (CYLT:YLT = 3.63). Previous studies found that N-glycosylated aminopeptidases exhibited higher thermal stability and catalytic efficiency . This study demonstrated that N-glycosylation would promote aminopeptidase catalysis to increase the level of protein degradation in CYLT.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies found that Nglycosylated aminopeptidases exhibited higher thermal stability and catalytic efficiency. 49 This study demonstrated that Nglycosylation would promote aminopeptidase catalysis to increase the level of protein degradation in CYLT.…”
Section: Legumainmentioning
confidence: 80%
“…Furthermore, in certain cases, along with the metagenomic approach 29 , it is possible to identify new enzymes with high biotechnological potential in a sea of bioinformatics data. Some thermo-tolerant 52 , solvent-tolerant 20 and halo-tolerant 53 aminopeptidases have been reported, however, none display all three features simultaneously (see Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aminopeptidase activity was determined according to Xi et al (2015) using 2 mM Arg-pNA as substrate suspended in 50 mM Tris-HCl, pH 7.0 at 40 °C for 10 min. The concentration of released p-nitroaniline was calculated using absorbance readings at 405 nm in a microplate reader (TECAN, Ma ¨nnedorf, Netherland).…”
Section: Aminopeptidase Activity Assaymentioning
confidence: 99%